2017
DOI: 10.1016/j.electacta.2017.11.105
|View full text |Cite
|
Sign up to set email alerts
|

A re-evaluation of Sn(II) phthalocyanine as a catalyst for the electrosynthesis of ammonia

Abstract: The electrosynthesis of ammonia from nitrogen and water is a topic of considerable interest in the quest for sustainable and decentralized NH 3 production. Tin(II) phthalocyanine complexes have been proposed as electrocatalysts for nitrogen reduction to ammonia in aqueous solution, with Faradaic yields approaching 2% having been reported. Herein, however, we show that such complexes are not electrocatalysts for this transformation, with the amount of ammonia detected being essentially the same under N 2 and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…immersing an electrode into a solution), or upon electrochemical stimuli. For example, materials like nitrides 24,25 and phthalocyanines 26 that have been tested as NRR catalysts were all found to decompose under reductive potentials with the formation of ammonia through a non-electrocatalytic reaction in aqueous electrolytes.…”
Section: Potential Origins Of False Nrr Positivesmentioning
confidence: 99%
“…immersing an electrode into a solution), or upon electrochemical stimuli. For example, materials like nitrides 24,25 and phthalocyanines 26 that have been tested as NRR catalysts were all found to decompose under reductive potentials with the formation of ammonia through a non-electrocatalytic reaction in aqueous electrolytes.…”
Section: Potential Origins Of False Nrr Positivesmentioning
confidence: 99%
“…Recent retests of some reported catalysts have demonstrated that the NH 3 are originated from contaminants or decomposition of catalysts rather than from NRR. [ 100 ] To avoid these false positive results during NRR, establishing benchmarking protocols for control experiments and ammonia measurements have been proposed by several groups. [ 101 ] In addition to the difficulty of accurately detecting NRR‐generated NH 3 , the current most important issues in NRR electrocatalysis involve acquiring desirable activity and selectivity.…”
Section: Porous Nrr Electrocatalystsmentioning
confidence: 99%
“…Finally, the commendable effort of Shipman and Symes whose report refutes the previously published activity of Sn(II) phthalocyanine on carbon foil in a 1 M KOH solution [46] should be mentioned. The group found that substituting the N 2 feed with Ar resulted in the same rate of NH 3 formation, proving that the source of NH 3 was not the NRR but the decomposition of the catalyst-electrode.…”
Section: Recent Experimental Findingsmentioning
confidence: 88%